Anthocyanins from Purple Corn Ameliorated Tumor Necrosis Factor‐α‐Induced Inflammation and Insulin Resistance in 3T3‐L1 Adipocytes via Activation of Insulin Signaling and Enhanced GLUT4 Translocation. Issue 12 (19th September 2017) - Luna‐Vital, Diego; Weiss, Matthew; Gonzalez de Mejia, Elvira
Abstract : Scope: The aim was to compare the effect of an anthocyanin‐rich extract from purple corn pericarp (PCW) and pure anthocyanins on adipogenesis, inflammation, and insulin resistance in 3T3‐L1 adipocytes on basal and inflammatory conditions. Methods and results: Preadipocytes (3T3‐L1) were treated during differentiation with or without PCW. Differentiated adipocytes were treated either individually or in combination with tumor necrosis factor α (TNF‐α) and PCW, or pure C3G, Pr3G, P3G. PCW reduced preadipocyte differentiation (IC50 = 0.4 mg/mL). PCW and pure anthocyanins including C3G reduced fatty acid synthase enzymatic activity. PCW reduced TNF‐α‐dependent inflammatory status increasing adiponectin (39%), and decreasing leptin (−79%). PCW and C3G increased glucose uptake and reduced reactive oxygen species generation in insulin resistant adipocytes. An increase in phosphorylation was observed in AKT, IKK, and MEK, and a decrease in IRS and mTOR activating the insulin receptor‐associated pathway. PCW (7.5‐fold) and C3G (6.3‐fold) enhanced GLUT4 membrane translocation compared to insulin resistant adipocytes. Conclusion: Anthocyanins from colored corn prevented adipocyte differentiation, lipid accumulation, and reduced PPAR‐γ transcriptional activity on adipocytes in basal conditions. Ameliorated TNF‐α‐induced inflammation and insulin resistance in adipocytes via activation of insulin signaling and enhanced GLUT4 translocation suggesting a reduced hyperglycemia associated with the metabolic syndrome. Abstract : Obesity and diabetes are becoming more and more prevalent around the world. Obese individuals have far more adipose tissue than a healthy individual. Highly colored fruits and vegetables contain flavonoid compounds such as anthocyanins. Anthocyanin‐rich foods clearly illustrate the potential health benefits they contain through their impact in obesity and insulin‐resistance diseases. The results of this research suggest, for the first time, that the anthocyanins present in purple corn can promote beneficial effects against obesity and its complications.